Without a conflict model of electron - Tchaban, Vasil (Вопросы атомной науки и техники, 2019)
The model of electron is oﬀered with quark distribution of charge density and ”white hole” (on similarity of ”black hole” in gravitation) in a center. Such structure abolishes the crisis of electromagnetic mass, calculated on universal formula and on the impulse of the electromagnetic ﬁeld. A model in order to please a classic electrodynamics keeps monolithic nature of elementary particle, and in order to please a quantum allows the separate charged zones to interpret as separate quarks. Coming from harmony of spheres of the separate charged zones, a white hole can be interpreted as white (neutral) quark conditionally in addition to three coloured. As after the electric radius re = 1.185246·10⁻¹⁵ m of white hole the laws of electricity do not operate, then the crisis of point charge is removed at the same time too, because of must be: r ≥ re. Запропоновано модель електрона з кварковим розподілом густини заряду й "білою дірою" (на подобу "чорної діри" в ґравітації) у центрі. Така структура скасовує кризу електромаґнітної маси, обчисленої за універсальною формулою енергії і за імпульсом електромаґнітного поля. Модель на догоду класичній електродинаміці зберігає монолітність елементарної частинки, а на догоду квантовій -- дозволяє окремі заряджені зони трактувати як окремі кварки. Виходячи з гармонії сфер окремих заряджених зон, "білу діру" можна умовно трактувати як білий (нейтральний) кварк на додаток до трьох кольорових (?). Оскільки за електричним радіусом "білої діри" re = 1.185246·10⁻¹⁵ m закони електрики не діють, то водночас знімається криза точкового заряду, як нереального, бо мусить бути r ≥ re . Предложена модель электрона с кварковым распределением плотности заряда и "белой дырой" (на подобие "черной дыры" в гравитации) в центре. Такая структура устраняет кризис электромагнитной массы, вычисленной по универсальной формуле энергии и через импульс электромагнитного поля. Модель на удовлетворение классической электродинамике сохраняет монолитность элементарной частицы, а на удовлетворение квантовой -- разрешает отдельные заряженные зоны рассматривать как отдельные кварки. Исходя из гармонии сфер отдельных заряженных зон, "белую дыру" можно условно рассматривать как белый (нейтральный) кварк в дополнение до трех цветных (?). Поскольку за электрическим радиусом "белой дыры" re = 1.185246·10⁻¹⁵ m законы електричества не действуют, то одновременно устраняется кризис точковости заряда, как недействительного, ибо должно быть r ≥ re .